ISOTOPE Sm-Nd DATA ON THE LATE SILURIAN-EARLY DEVONIAN AGE OF DYNAMOMETAMORPHISM AT THE BASE OF OPHIOLITIC ALLOCHTHON IN THE SAKMARA ZONE OF THE SOUTHERN URALS - Pushkarev E.V.; Biryuzova A.P.; Serov P.A. (My University, 2007)
Most ophiolitic complexes occur in present-day structures as allochthonous sheets that are thrust over only slightly metamorphosed sedimentary and volcanic complexes of continental margins. The base of such thrusts is commonly composed of high-grade metamorphic rocks up to granulites. The inverted metamorphic zoning at the base of nappes demonstrates the increase in PT gradients from bottom to top approaching ultramafic rocks. Another important attribute of such complexes is development of recumbent, isoclinal, and disharmonic drag folds. The thickness of metamorphic rocks at the base of allochthons does not exceed 1–2 km. While the relatively young and still hot oceanic crust is participating in thrusting, the thermal gradients in the metamorphic base reach 1000°C/km or more. There is every reason to suggest that the age of high-gradient metamorphism corresponds to the age of thrusting. Because isotopic dating of ophiolites meets methodological difficulties, the timing of metamorphism at their base may be used for estimation of the age of thrusting. Precisely this problem has been set and solved for the metamorphic aureole at the base of the Khabarny mafic–ultramafic allochthon in the Sakmara Zone of the southern Urals.
Keywords: Devonian; Silurian; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Silurian; Палеозой::Силурийская